2009
DOI: 10.1172/jci36745
|View full text |Cite
|
Sign up to set email alerts
|

Eptifibatide-induced thrombocytopenia and thrombosis in humans require FcγRIIa and the integrin β3 cytoplasmic domain

Abstract: Thrombocytopenia and thrombosis following treatment with the integrin αIIbβ3 antagonist eptifibatide are rare complications caused by patient antibodies specific for ligand-occupied αIIbβ3. Whether such antibodies induce platelet clearance by simple opsonization, by inducing mild platelet activation, or both is poorly understood. To gain insight into the mechanism by which eptifibatide-dependent antibodies initiate platelet clearance, we incubated normal human platelets with patient serum containing an αIIbβ3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 80 publications
3
55
0
1
Order By: Relevance
“…The activation of the GPIIb/IIIa receptor is a common final step of platelet aggregation in response to various agonists, after which αIIbβ3 binds to soluble fibrinogen and bridges platelets, leading to platelet aggregation [34] . Antagonists of the GPIIb/IIIa receptor inhibit platelet aggregation induced by various agonists by preventing fibrinogen from binding to activated GPIIb/IIIa receptors [35] . Psm2 inhibited ADP-, thrombin-, U46619-, and collagen-induced platelet aggregation and blocked platelet adhesion to immobilized fibrinogen and collagen without affecting the binding of the GPIIb/IIIa receptor to fibrinogen, which suggested that Psm2 affects inside-out platelet signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the GPIIb/IIIa receptor is a common final step of platelet aggregation in response to various agonists, after which αIIbβ3 binds to soluble fibrinogen and bridges platelets, leading to platelet aggregation [34] . Antagonists of the GPIIb/IIIa receptor inhibit platelet aggregation induced by various agonists by preventing fibrinogen from binding to activated GPIIb/IIIa receptors [35] . Psm2 inhibited ADP-, thrombin-, U46619-, and collagen-induced platelet aggregation and blocked platelet adhesion to immobilized fibrinogen and collagen without affecting the binding of the GPIIb/IIIa receptor to fibrinogen, which suggested that Psm2 affects inside-out platelet signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of thrombocytopenia is thought to be the formation of a neoepitope on GPIIbIIIa, which becomes the target of naturally-occurring antibodies or antibodies induced by prior exposure to the drug [23]. In addition to causing platelet clearance, eptifibatidedependent anti-platelet antibodies have been shown to induce platelet activation through platelet FcγRIIa receptor binding, which may explain the occurrence of thrombosis in some patients with eptifibatide-thrombocytopenia [24].…”
Section: Fiban-dependent Antibodiesmentioning
confidence: 99%
“…19,20 All other blood samples from healthy volunteers who had not taken any anticoagulant in the past 2 weeks were donated as approved by the Institutional Review Board of the BloodCenter of Wisconsin, and informed consent was obtained in accordance with the Declaration of Helsinki. Blood was drawn into sodium citrate, pH 7.4, supplemented with 50 ng/mL prostaglandin E1 (PGE 1 ) and spun at 200g for 10 minutes.…”
Section: Platelet Isolationmentioning
confidence: 99%
“…Pretreatment with eptifibatide and/or abciximab also suppressed Akt phosphorylation in platelets exposed to either soluble heparin ( Figure 4B) or immobilized heparin (supplemental Figure 4), as well as their ability to spread on immobilized fondaparinux (supplemental Figure 2C). Finally, platelets from a patient with Glanzmann thrombasthenia that expressed 100% levels of a mutant ␣IIb␤3 complex lacking much of the ␤3 cytoplasmic domain 19,20 failed to increase the phosphorylation of Akt on exposure to soluble UFH ( Figure 4C). Taken together, these data demonstrate that the mechanism by which heparin potentiates platelet activation is via outside-in signaling through the major platelet integrin, ␣IIb␤3 ( Figure 5).…”
mentioning
confidence: 99%